A knowledge-based hypertext expert system for the quality control of concrete - Dawood, Salman; Ogunlana, Stephen O.; Prapon Phasukyud; Worsak Kanok-Nukulchai; Sugiyama, Toshiyuki; The Government of Norway (Bangkok : Asian Institute of Technology, 1993)
A prototype computer-based system is developed which combines and links different documents about quality control together and stores all the information at the different levels of details. In addition, this system acts like an expert giving advice to inexperienced personnel and helping them solve quality control problems. Hypertext and expert systems are the two approaches that assist the author to develop this system. The research is aimed at developing a system for use in controlling quality of concrete. However, "Intelligent Quality Control System" covers the methods of quality control adminis tration, testing, inspection, tracking, docu111enting, etc. KnowledgePro is found to be an appropriate tool for developing this system. I tis knowledge processing environment that combines hypertext, and a variety of Artificial Intelligent techniques. The conceptual model of the system is decomposed into four independent modules: Quality Control Manual, Work Procedures, Inspection Manual and Delegation of Responsibilities and Authorities that can be independently run by the user. The Q. C. Manual outlines procedures which not only reflect quality policies but the manual includes a flow diagram for Q. C. of conctete. Each event on the diagram has explanations in hypertext documentations. The modules, named 'Work Procedures' is fmther decomposed into concrete production procedures, pre-concreting, dming concreting and post concreting operations. The procedures are supported by different "Intelligent Forms" for documentation. The system gives recom mendations for mixing, handling, transporting, and consolidation of concrete, expert advice for selection of admixtures, hot weather concreting, curing concreting, expert system for cold weather concreting, expert system for strength evaluation of concrete and many more. The module, 'Inspection Manual' is designed in the form of a checklist flow diagram in graphical presentations. Hyper-region defines each task on the checklist which is connected with the knowledge base. A Linear Responsibility Chart showing delegation of responsibilities and authorities of the organization of the owner, engineer, contractor, and regulating agency involved in the project is included in the system in pictorial fo1m as well as explanations are provided in hypertext documentation.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1993
Keywords: Expert systems (Computer science); Concrete -- Quality control